The Legality of the Defensive Measures Taken by the USA and the UK in Response to the Houthi Attacks - Glavica, Patricija; Brulc, Leon (LeXonomica, 2024)
The article delves into the legality of defensive actions taken by the USA and the UK in response to the Houthi attacks in the Red Sea. Despite assertions that such actions are justified under the right to self-defence, legal ambiguities persist in international law. The authors argue that while attacks on merchant vessels by non-state actors may constitute armed aggression, clarity is lacking on whether they meet the criteria for self-defence. The USA and UK stress that attacks on their warships validate their defensive measures, framing them as necessary responses to significant threats. However, the authors contend that the principle of proportionality may have been disregarded, urging restraint in the use of force to safeguard ships while respecting Yemen’s sovereignty. The article underscores the need for a nuanced approach to assessing the legality and necessity of military actions in complex conflict scenarios. Povzetek Članek obravnava zakonitost obrambnih ukrepov ZDA in Združenega kraljestva kot odziv na napade Hutijev v Rdečem morju. Kljub trditvam, da so takšni ukrepi upravičeni na podlagi pravice do samoobrambe, v mednarodnem pravu še vedno obstajajo pravne nejasnosti. Avtorja trdita, da čeprav lahko napadi nedržavnih akterjev na trgovska plovila pomenijo oboroženo agresijo, ni jasno, ali izpolnjujejo merila za samoobrambo. ZDA in Združeno kraljestvo poudarjata, da napadi na njune vojaške ladje potrjujejo njune obrambne ukrepe, saj jih opredeljujeta kot nujen odziv na pomembne grožnje. Avtorja prispevka ugotavljata, da morda ni bilo upoštevano načelo sorazmernosti, in pozivata k zadržanosti pri uporabi sile za zaščito ladij ob spoštovanju suverenosti Jemna. Članek poudarja potrebo po diferenciranem pristopu k ocenjevanju zakonitosti in nujnosti vojaških ukrepov v zapletenih konfliktnih scenarijih.